Neptus - A framework to support multiple vehicle operation - Paulo Sousa Dias (2005)
This paper describes the development of a C3I (communications, command, control and intelligence/information) infrastructure, taking place at the Underwater Systems and Technology Laboratory (LSTS) of FEUP. This infrastructure, the Neptus framework, goal is to support the coordinated operation of heterogeneous teams, which include autonomous and remotely operated underwater, surface, land, and air vehicles and people. People perform a fundamental role, not only in the case of remotely operated vehicles, but also with autonomous vehicles where mix-initiative operation is a requirement. The operational scenarios for these teams are mainly environmental monitoring missions but could also include environmental disaster scenarios, rescue missions, etc. The Neptus distributed architecture is service oriented, which enables high degrees of interoperability between applications, of scalability (number of nodes), and of reconfiguration (number and type of nodes).